Social isolation perturbs experience‐driven synaptic glutamate receptor subunit 4 delivery in the developing rat barrel cortex. Issue 10 (20th March 2013) - Miyazaki, Tomoyuki; Kunii, Misako; Jitsuki, Susumu; Sano, Akane; Kuroiwa, Yoshiyuki; Takahashi, Takuya
Abstract In neonates, the stress of social isolation can alter developing neural circuits and cause mental illness. However, the molecular and cellular bases for these effects are poorly understood. Experience‐driven synaptic AMPA receptor delivery is crucial for circuit organisation during development. In the rat, whisker experience drives the delivery of glutamate receptor subunit 4 (GluA4) but not glutamate receptor subunit 1 (GluA1) to layer 4–2/3 pyramidal synapses in the barrel cortex during postnatal day (P)8–10, whereas GluA1 but not GluA4 is delivered to these synapses during P12–14. We recently reported that early social isolation disrupts experience‐driven GluA1 delivery to layer 4–2/3 pyramidal synapses during P12–14. Here, we report that neonatal isolation affects even earlier stages of development by preventing experience‐dependent synaptic GluA4 delivery. Thus, social isolation severely affects synaptic maturation throughout early postnatal development.